Characterisation and properties of Cu2ZnSnS4 thin films synthesised by sputtering from an alloy target. (23rd February 2017) - Zhou, Haifang; Cheng, Shuying; Zhao, Pengyi; Yu, Jinling; Jia, Hongjie
Abstract : Cu2 ZnSnS4 (CZTS) thin films were synthesised on glass substrates by sulphurising sputtered metallic precursors in H2 S + N2 atmosphere at 500 °C. The influences of the radio frequency (RF) sputtering power on the structure, surface morphology, optical and electrical properties of the thin films were investigated. Scanning electron microscopy, X-ray diffraction, Raman and UV–vis NIR spectroscopy were used to characterise the films. All the CZTS thin films exhibited a dominant kesterite structure. With increasing sputtering power, secondary phases in the films reduced, and the surface became more compact. The optimum quality films with poor-Cu and rich-Zn were obtained when the sputtering power was 90 W, and the optical band gap, carrier concentration, resistivity and mobility were 1.47 eV, 2.07 × 10 18  cm −3, 2.37 Ω cm and 1.38 cm 2  s −1  v −1, respectively. The optical and electrical properties of the CZTS thin films in relation to the secondary phases were discussed.